1989
DOI: 10.1128/mcb.9.7.3105
|View full text |Cite
|
Sign up to set email alerts
|

Each of the conserved sequence elements flanking the cleavage site of mammalian histone pre-mRNAs has a distinct role in the 3'-end processing reaction.

Abstract: To study the substrate requirements for the histone 3'-end processing reaction of mammalian histone pre-mRNAs, we created a set of mutations in the sequences flanking the processing site of a mouse H3 gene. We found that deletion of the downstream purine-rich element hypothesized to interact with U7 small nuclear RNA abolishes in vitro 3'-end processing. Somewhat surprisingly, however, mutations in the hairpin loop element which destabilize or destroy the secondary structure reduce but do not abolish 3'-end pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 30 publications
3
35
0
Order By: Relevance
“…Replication-dependent histone mRNAs contain a 26-nt stem-loop structure at their 39 terminus+ The sequence of the stem-loop, as well as the sequence immediately flanking the stem-loop, is highly conserved among all metazoans+ SLBP is found associated with this stemloop in both the nucleus and cytoplasm of higher eukaryotes (Mowry et al+, 1989;Vasserot et al+, 1989;Pandey et al+, 1991;Hanson et al+, 1996;Martin et al+, 1997)+ Mutations that disrupt formation of the SLBP-RNA complex in nuclear extract interfere with proper pre-mRNA processing, as well as mature mRNA localization and cell-cycle dependent stability (Pandey & Marzluff, 1987;Harris et al+, 1991;Sun et al+, 1992;Streit et al+, 1993;Williams et al+, 1994;Dominski et al+, 1995)+ Here we have used direct K d measurements with purified protein and RNA components to define the affinity and specificity of the SLBP-histone mRNA interaction+ Nitrocellulose filter-binding experiments were performed to determine the affinity of SLBP for the RNA stem-loop+ This interaction was found to be quite tight, with a K d ϭ 1+5 nM, corresponding to a ⌬G of Ϫ12+0 kcal/mol+ The measured affinity was strongly affected by ionic strength, dropping off quickly with increasing concentrations of MgCl 2 or KCl (Fig+ 2)+ This suggests that electrostatics play a key role in recognition of the stem-loop by SLBP, similar to what is commonly observed for many complexes involving protein recognition of a simple DNA duplex (Misra et al+, 1994)+ However, even at very high salt concentration (800 mM KCl), binding was still relatively tight (60 nM), suggesting that hydrophobics contribute to the interaction, perhaps through recognition of the loop or flanking nucleotides+ As observed previously in extracts, mutations in the 6-bp stem greatly reduced SLBP binding (Fig+ 3A)+ The bottom 2 bp are invariantly G-C base pairs+ Previous work had shown a large drop in binding affinity upon transversion of the bottom two G-C base pairs together (Williams & Marzluff, 1995)+ We found that transversion of the bottom base pair alone had no detectable effect on binding, whereas transversion of the second base pair (G7-C20) led to a marked increase in the K d + In addition, we found that mutation of the third base pair, always a pyrimidine-purine pair, to G-C also had a strong, negative effect on binding+ Similarly, mutation of the invariant U-A pair at the top of the stem had a dramatic deleterious effect on SLBP binding+ Taken together, these data suggest multiple SLBP contacts to the RNA stem, particularly to base pairs G7-C20, C8-G19, and U11-A16 (Fig+ 5)+ Some of these effects could result from subtle changes in the helical parameters that reposition specificity determinants in the loop relative to the base of the stem or flanking regions+…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Replication-dependent histone mRNAs contain a 26-nt stem-loop structure at their 39 terminus+ The sequence of the stem-loop, as well as the sequence immediately flanking the stem-loop, is highly conserved among all metazoans+ SLBP is found associated with this stemloop in both the nucleus and cytoplasm of higher eukaryotes (Mowry et al+, 1989;Vasserot et al+, 1989;Pandey et al+, 1991;Hanson et al+, 1996;Martin et al+, 1997)+ Mutations that disrupt formation of the SLBP-RNA complex in nuclear extract interfere with proper pre-mRNA processing, as well as mature mRNA localization and cell-cycle dependent stability (Pandey & Marzluff, 1987;Harris et al+, 1991;Sun et al+, 1992;Streit et al+, 1993;Williams et al+, 1994;Dominski et al+, 1995)+ Here we have used direct K d measurements with purified protein and RNA components to define the affinity and specificity of the SLBP-histone mRNA interaction+ Nitrocellulose filter-binding experiments were performed to determine the affinity of SLBP for the RNA stem-loop+ This interaction was found to be quite tight, with a K d ϭ 1+5 nM, corresponding to a ⌬G of Ϫ12+0 kcal/mol+ The measured affinity was strongly affected by ionic strength, dropping off quickly with increasing concentrations of MgCl 2 or KCl (Fig+ 2)+ This suggests that electrostatics play a key role in recognition of the stem-loop by SLBP, similar to what is commonly observed for many complexes involving protein recognition of a simple DNA duplex (Misra et al+, 1994)+ However, even at very high salt concentration (800 mM KCl), binding was still relatively tight (60 nM), suggesting that hydrophobics contribute to the interaction, perhaps through recognition of the loop or flanking nucleotides+ As observed previously in extracts, mutations in the 6-bp stem greatly reduced SLBP binding (Fig+ 3A)+ The bottom 2 bp are invariantly G-C base pairs+ Previous work had shown a large drop in binding affinity upon transversion of the bottom two G-C base pairs together (Williams & Marzluff, 1995)+ We found that transversion of the bottom base pair alone had no detectable effect on binding, whereas transversion of the second base pair (G7-C20) led to a marked increase in the K d + In addition, we found that mutation of the third base pair, always a pyrimidine-purine pair, to G-C also had a strong, negative effect on binding+ Similarly, mutation of the invariant U-A pair at the top of the stem had a dramatic deleterious effect on SLBP binding+ Taken together, these data suggest multiple SLBP contacts to the RNA stem, particularly to base pairs G7-C20, C8-G19, and U11-A16 (Fig+ 5)+ Some of these effects could result from subtle changes in the helical parameters that reposition specificity determinants in the loop relative to the base of the stem or flanking regions+…”
Section: Discussionmentioning
confidence: 99%
“…Most eukaryotic mRNAs are polyadenylated at their 39 ends, providing a binding site for several nuclear and cytoplasmic protein factors+ These factors control the transport of mRNA from the nucleus, targeting to polyribosomes for translation, and regulation of message stability+ The replication-dependent histone mRNAs are the only RNA polymerase II transcripts that lack this poly(A) tail+ Instead, the histone pre-mRNAs contain two highly conserved regions at their 39 terminus: a 26-nt stem-loop structure followed by a purine-rich sequence known as the histone downstream element (HDE; Birnstiel et al+, 1985;Marzluff, 1992)+ These premRNAs are processed in the nucleus by a single endonucleolytic cleavage approximately 5 nt downstream of the stem-loop, catalyzed by the U7 snRNP through base pairing of the U7 snRNA with the HDE (Gick et al+, 1986)+ After processing, the mature messages are exported from the nucleus to the cytoplasm, where they are targeted to polyribosomes and translated (Fig+ 1; Eckner et al+, 1991;Sun et al+, 1992;Williams et al+, 1994)+ These events are tightly coupled to the cell cycle, resulting in high histone mRNA levels immediately preceding DNA replication+ This posttranscriptional regulation is responsible for the majority of the cell-cycle dependent control of histone mRNA levels (Schumperli, 1986;Marzluff & Pandey, 1988;Harris et al+, 1991)+ The stem-loop binding protein (SLBP), a 32-kDa protein with no known homologs, is associated with the stem-loop at the 39 end of the histone messages in both the nucleus and cytoplasm of higher eukaryotes (Fig+ 1; Mowry et al+, 1989;Vasserot et al+, 1989;Pandey et al+, 1991;Hanson et al+, 1996;Martin et al+, 1997)+ SLBP levels are cell-cycle regulated, being highest during S-phase when histone mRNA levels are increased (Whitfield et al+, 2000)+ SLBP is necessary for efficient 39 end processing of histone pre-mRNA by the U7 snRNP (Streit et al+, 1993;Dominski et al+, 1995)+ In addition, mutations in the stem-loop that disrupt formation of the SLBP-RNA complex result in the retention of the mRNA in the nucleus and failure to target to polyribosomes (Sun et al+, 1992;Williams et al+, 1994)+ These same mutations also disrupt the cell-cycle dependent regulation of histone mRNA stability (Pandey & Marzluff, 1987; Harris et al+, 1991)+ Through these mecha-nisms, it is believed that formation and maintenance of the SLBP-RNA complex contributes to the cell-cycle regulation of histone levels in higher eukaryotes+ Formation of the SLBP-histone mRNA complex has been previously studied using competition assays in nuclear extract …”
Section: Introductionmentioning
confidence: 99%
“…In sea urchins, the HDE has a highly conserved sequence CAAGAAAGA (Birchmeier et al, 1983). In vertebrate histone pre-mRNAs, the HDE is more variable although it contains a purine-rich core that resembles the HDE sequence of sea urchins Cotten et al, 1988;Mowry et al, 1989;Mowry and Steitz, 1987b). The endonucleolytic cleavage occurs between the two elements, after the fourth (sea urchins) or the fifth nucleotide (mammals) downstream of the stem-loop, which is typically an adenosine, yielding the mature histone mRNA that ends with the stem-loop followed by a short single stranded tail (Fig.…”
Section: Sequence Elements In 3' End Processing Of Histone Pre-mrnasmentioning
confidence: 99%
“…Two sequence elements required for processing that usually lie within 100 nucleotides downstream of the stop codon have been identified in both sea urchin (Birchmeier et al, 1982;Birchmeier et al, 1983;Birchmeier et al, 1984) and mammalian histone pre-mRNAs (Birchmeier et al, 1984;Cotten et al, 1988;Mowry et al, 1989;Mowry and Steitz, 1987a;Vasserot et al, 1989). The first element is a stem-loop, and the second; a purine-rich histone downstream element (HDE) that begins 15-20 nucleotides 3' of the stem-loop (Fig.…”
Section: Sequence Elements In 3' End Processing Of Histone Pre-mrnasmentioning
confidence: 99%
“…Histone pre-mRNA processing requires two defined trans-acting factors, U7 snRNP, which is absolutely required for processing (Mowry and Steitz 1987b;Cotten et al 1988) and HBF, which is not absolutely required for processing in vitro (Mowry et al 1989;Streit et al 1993). The degree of dependence of processing on HBF is variable with different extracts and with different substrates (Streit et al 1993).…”
Section: Depletion Of Slbp Reduces the Efficiency Of Histone Pre-mrnamentioning
confidence: 99%